2009
DOI: 10.1007/s11661-009-9962-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Laser Weldability of INCONEL 738 Superalloy through Microstructural Modification

Abstract: Microstructural study of laser-beam-welded IN 738 superalloy was carefully performed to better understand the causes of heat-affected zone (HAZ) cracking and to determine an improved approach of alleviating the weldability problem. The HAZ cracks in the alloy were intergranular liquation cracks that resulted from the liquation reaction of both secondary solidification products (MC carbides and c-c¢ eutectic) and solid-state reaction products (c¢ particles) present in the preweld material. In contrast to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 25 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…Moreover, some local sites consisted of very high Cr and Mo concentrations along with high B intensity, suggesting that fine boride particles might be formed at such sites. The presence of borides is reported to facilitate liquation at low temperature and enlarge the brittle temperature range, thus increasing the susceptibility of HAZ liquation cracking [22]. The cast Mar-M004 superalloy comprised of complex solidification products at the interdendritic boundaries.…”
Section: Haz Microcrack Inspection and Phase Identificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, some local sites consisted of very high Cr and Mo concentrations along with high B intensity, suggesting that fine boride particles might be formed at such sites. The presence of borides is reported to facilitate liquation at low temperature and enlarge the brittle temperature range, thus increasing the susceptibility of HAZ liquation cracking [22]. The cast Mar-M004 superalloy comprised of complex solidification products at the interdendritic boundaries.…”
Section: Haz Microcrack Inspection and Phase Identificationsmentioning
confidence: 99%
“…Liquidation cracking in the HAZ is one of the most noticeable problems in welding or repair-welding of Ni-based superalloys such as IN 738 [7][8][9], Rene 80 [10][11][12][13], IN 939 [14,15], RR 1000 [16], IN 713C [17], and K465 [18]. Grain boundary liquation results from incipient melting of MC carbides, Cr-Mo borides, γ-γ eutectic and Ni-Zr intermetallics along the solidified boundaries [18][19][20][21][22][23][24]. The use of filler metals with (a) slower aging response, (b) smaller lattice mismatch between the precipitates and the matrix, (c) lowered (Ti + Al) concentrations and (d) softer weld metal have been reported to reduce the HAZ cracking susceptibility of IN 738LC welds [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabrication of new turbine components, as well as repair of service-damaged parts, made of conventionally cast and SX superalloys usually require joining by different welding techniques. However, IN 738, like other precipitation strengthened nickel base superalloys, is very difficult to weld due to its high susceptibility to heat-affected zone (HAZ) cracking during fusion welding processes [1,2]. HAZ cracking in IN 738 is attributed to the liquation of various phases in the alloy, subsequent wetting of grain boundaries by the liquid and decohesion along one of the solid-liquid interfaces due to oncooling tensile stresses [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, IN 738, like other precipitation strengthened nickel base superalloys, is very difficult to weld due to its high susceptibility to heat-affected zone (HAZ) cracking during fusion welding processes [1,2]. HAZ cracking in IN 738 is attributed to the liquation of various phases in the alloy, subsequent wetting of grain boundaries by the liquid and decohesion along one of the solid-liquid interfaces due to oncooling tensile stresses [2,3]. Similarly, weldability studies performed on fusion welded CMSX 486 superalloy showed that the alloy is highly susceptible to fusion zone cracking [4].…”
Section: Introductionmentioning
confidence: 99%